Effect of transverse magnetic fields on high-harmonic generation in intense laser–solid interaction. (31st August 2016) - Mu, J.; Li, F.-Y.; Sheng, Z.-M.; Zhang, J.
Abstract: The effect of transverse magnetic fields on surface high-harmonic generation in intense laser–solid interactions is investigated. It is shown that the longitudinal motion of electrons can be coupled with the transverse motion via the magnetic fields, which lead to even-order harmonics under normal laser incidence. The dependence of the coupling efficiency and hence even harmonic generation with preplasma scale length and magnetic field strength are presented based upon particle-in-cell simulations. When the magnetic field is parallel to the laser electric field, the spectral intensity of the second harmonic is proportional to the magnetic field strength in a wide range up to 160 MG, while the situation with the magnetic field perpendicular to the laser electric field is more complicated. The second harmonic generation due to the magnetic field also tends to increase with the plasma density scale lengths, which is different from the high-harmonic generation by the oscillating mirror mechanism. With the increase of the laser spot size from a laser wavelength λL, both the magnetic field-induced harmonics and oscillating mirror high harmonics tend to increase first and then become saturated after 3λL . The magnetic field-induced second harmonic may be used to evaluate large self-generated magnetic fields developed near the critical density region and the preplasma conditions.